Analiza błędów popełnionych w tłumaczeniu indonezyjskiego musicalu „Biarkan bintang menari” na język polski. - Zozula, Daria (Investigationes Linguisticae, 2009)
This article is to analyse the errors and mistakes (both technical and linguistic)made in the polish subtitles of an Indonesian musical “Biarkan bintang menari”. To fully analyze the errors a new, Indonesian language-specified typology was coined. It allows to explanation of the causes of every type of error found. The analysis is prefaced by a short introduction to Indonesian cinema in a whole and followed by a summary that emphasizes the conclusions. The aim of this paper is to stress the role of proof reading in the process of creating subtitles in a foreign language.